A chewable pediatric preparation of ibuprofen is palatable and acceptable to children. Issue 1 (10th February 2020) - Barnett, Steven; Bhatt, Aomesh
Abstract: The development of palatable and acceptable analgesics for children is a major challenge. Given the majority of medications are administered orally, and children are more sensitive to and less tolerant of bitterness, novel "child‐friendly" preparations need to be developed and tested specifically in this patient population. This study investigated the palatability and acceptability of a therapeutic dose of ibuprofen in the form of soft chewable capsules in 100 healthy children aged 7‐12 years of age and the acceptability of this novel preparation to their caregivers. About 97% of children adhered to a full therapeutic age‐related dose, with 72% of these participants rating the preparation as acceptable on a hedonic facial scale. Despite 22% of children noting a "hot, spicy, or burning" sensation, consistent with known chemesthetic effects of ibuprofen, 83% of children confirmed they would take the medication in future, which rose to 87% in the context of future illness. In addition, after observing their children ingesting the medication, 92% of parents/guardians confirmed that they would be happy to administer this preparation of ibuprofen to their child if they were unwell. In conclusion, ibuprofen administered in the form of soft chewable capsules was palatable and acceptable to the majority of children and their parents/guardians and may provide a convenient and easy to dose preparation to reduce fever and relieve pain in children.